Dysregulation of the miR‐194–CUL4B negative feedback loop drives tumorigenesis in non‐small‐cell lung carcinoma. Issue 3 (21st February 2017) - Mi, Jun; Zou, Yongxin; Lin, Xiaohua; Lu, Juanjuan; liu, Xiaochen; Zhao, Hui; Ye, Xiang; Hu, Huili; Jiang, Baichun; Han, Bo; Shao, Changshun; Gong, Yaoqin
Abstract : Cullin 4B (CUL4B), a scaffold protein that assembles CRL4B ubiquitin ligase complexes, is overexpressed in many types of cancers and represses many tumor suppressors through epigenetic mechanisms. However, the mechanisms by which CUL4B is upregulated remain to be elucidated. Here, we show that CUL4B is upregulated in non‐small‐cell lung carcinoma (NSCLC) tissues and is critically required for cell proliferation and migration in vitro and for xenograft tumor formation in vivo . We found that microRNA‐194 (miR‐194) and CUL4B protein were inversely correlated in cancer specimens and demonstrated that miR‐194 could downregulate CUL4B by directly targeting its 3′‐UTR. We also showed that CUL4B could be negatively regulated by p53 in a miR‐194‐dependent manner. miR‐194 was further shown to attenuate the malignant phenotype of lung cancer cells by downregulating CUL4B. Interestingly, CRL4B also epigenetically represses miR‐194 by catalyzing monoubiquitination at H2AK119 and by coordinating with PRC2 to promote trimethylation at H3K27 at the gene clusters encoding miR‐194. RBX1, another component in CRL4B complex, is also targeted by miR‐194 in NSCLC cells. Our results thus establish a double‐negative feedback loop between miR‐194 and CRL4B, dysregulation of which contributes to tumorigenesis. The function of miR‐194 as a negative regulator of CUL4B has therapeutic implications in lung cancer. Abstract : CUL4B is upregulated in lung cancer and contributes to malignancy. We found that CUL4B was targeted and negatively regulated by miR‐194. Interestingly, CRL4B ubiquitin ligase complexes, for which CUL4B acts as a scaffold, epigenetically repressed miR‐194. Thus, CRL4B and miR‐194 forms a double‐negative feedback loop in lung cancer.